CORPORATE SOCIAL RESPONSIBILITIES (CSR) PERFORMANCE OF SELECTED IT FIRMS IN CHENNAI - AN EXPLORATORY RESEARCH - Porkodi, T.; Venkatramaraju, D. (International Journal of Psychosocial Rehabilitation, 2020)
Historically businesses have always been known for their financial responsibility. Their main responsibility has been to make profits and increase shareholder value. It is only in last few decades that a radical change has taken place in the business whereby these businesses are expected to behave responsibly and take care of other stakeholders apart from their shareholders. This paradigm shift has happened due to the profound external and internal pressures by various stakeholders which have been experienced by the businesses. In today’s competitive scenario corporations that do not respond to these pressures and societal expectations risk losing legitimacy. Organizations are expected to be more ‘caring’ towards all the stakeholders. Slowly the business is beginning to accept the fact that it stands to gain from improved relationship with owners, customers, suppliers, employees and the surrounding environment.